2011
DOI: 10.1016/j.limno.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community structure and ecology of the tropical-highland Lake Hayq, Ethiopia

Abstract: a b s t r a c tLake Hayq, a highland lake in Ethiopia, was stocked with Tilapia fish (Oreochromis niloticus) in late 1970s, offering an opportunity to study the effect of fish predation in a natural lake. Since 1930s, some limnological surveys have been done sporadically documenting a change in zooplankton composition including the disappearance of cladocerans, hypothesizing the stocked planktivorous fish could be a cause. Nevertheless, no detailed research was conducted to identify potential effects of fish s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
(64 reference statements)
8
20
2
Order By: Relevance
“…For instance several fish kill outbreaks occurred in 2005 in which three peaks of mortality at an interval of one month were recorded in Northern Europe (Castro et al, 2006). Similar evidence of mass fish kill has also been reported recently from Lake Hayq in northern Ethiopia (Fetahi et al, 2011).…”
Section: Introductionsupporting
confidence: 75%
“…For instance several fish kill outbreaks occurred in 2005 in which three peaks of mortality at an interval of one month were recorded in Northern Europe (Castro et al, 2006). Similar evidence of mass fish kill has also been reported recently from Lake Hayq in northern Ethiopia (Fetahi et al, 2011).…”
Section: Introductionsupporting
confidence: 75%
“…The pelagic zooplankton standing biomass in Lake Wonchi showed seasonal variation and positive correlation with Chl-a concentrations, which mirrors a bottom-up effect of phytoplankton on zooplankton dynamics in the lake, which has also been documented elsewhere (Brooks and Dodson, 1965;Jeppesen et al, 1997). The decline in zooplankton biomass during the rainy season was likely caused by low abundance of total copepodites during this period (abundance: dry season 118x10 3 Ind m (Wondie and Mengistu, 2006;Dagne et al, 2008;Fetahi et al, 2011;Haileselasie et al, 2012). The zooplankton abundance of Lake Wonchi was dominated by Thermocyclops ethiopiensis (50%) and cladocerans (38%), which is in agreement with several other authors, who also reported low abundance of rotifers compared to crustacean in other highmountain tropical lakes (Gillooly and Dodson, 2000;Fetahi et al, 2011;Dejenie et al, 2012;Haileselasie et al, 2012).…”
Section: Spatio-temporal Patterns In the Zooplankton Community And Bisupporting
confidence: 64%
“…Some studies were able to explore zooplankton associations along ecosystem gradients mainly in the rift valley region and the Bishoftu crater lakes (Wodajo and Belay, 1984;Green and Mengestou, 1991;Mengestou and Fernando, 1991;Vijverberg et al, 2014). However, compared to rift valley and Bishoftu crater lakes, zooplankton from highland lakes in Ethiopia have been studied only sporadically, with only a few exceptions (Dejen et al, 2013;Fetahi et al, 2011;Dejenie et al, 2012). This is particularly true of the deep crater Lake Wonchi in the central highlands which has never been investigated in detail to the best of our knowledge, presumably due to seclusion and lack of infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…The small size of individuals is also known to be related to a topdown predation effect (Fetahi et al, 2011). Amazonian reservoirs were often dominated by Rotifers the years following the first filling (Arcifa, 1984) but they were not abundant in our survey.…”
Section: Zooplankton Community Dynamics In the Nt2 Reservoirmentioning
confidence: 88%
“…Freshwater zooplankton communities have been described in tropical and sub-tropical areas in numerous studies in South America (Matsumura-Tundisi & Tundisi, 1976;Bini et al, 1997;Starling, 2000;Fernando, 2002;Bonecker et al, 2007;Lansac-Tôha et al, 2008;Sousa et al, 2014), Africa (Uku & Mavuti, 1994;Mageed & Heikal, 2006;Fetahi et al, 2011) and Asia (Dussart et al, 1984). They are, in lentic zones, generally driven by environmental factors such as turbidity, nutrient and dissolved oxygen concentrations or phytoplankton density and diversity (Hart, 1990;Schulz & Sterner, 1999).…”
Section: Introductionmentioning
confidence: 99%